PENGARUH ONLINE CUSTOMER REVIEW , KEPERCAYAAN, DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi terhadap Mahasiswa pengguna Platform Pasar Online) - Lailatul Istiqomah; Usman Usman (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The marketplace is a platform that acts as an intermediary between sellers and buyers to carry out buying and selling transactions online. The marketplace also provides various product selections according to category, payment method, estimated delivery, and many other features. The purpose of this study is to find out how much influence the online customer review, trust, and risk perception have on purchasing decisions with buying interest as an intervening variable (study of students using online market platforms). The sample in this study amounted to 150 respondents using the purposive sampling technique. The data collection method used is by distributing online questionnaires via a google form. The type of research method used is quantitative. The data analysis technique used is the structural equation of modeling (SEM). The results of this study indicate that: (1) Online Customer Review has a significant and positive effect on Purchase Interest; (2) Trust has a significant and positive effect on Purchase Interest; (3) Risk Perception does not influence Purchase Interest; (4) Online Customer Review has a significant and positive effect on Purchase Decisions; (5) Trust has a significant and positive effect on Purchase Decisions; (6) Risk Perception has a significant and negative effect on Purchase Decisions; and (7) Buying interest has a significant and positive effect on Purchase Decisions.